Qualitative Phytochemical Profiling and In Vitro Antioxidant Potential Evaluation of South African Momordica Balsamina Linn Fruit Pulp - Buang Matseke; Sipho Mapfumari; Mmamosheledi Mothibe (Life)
Momordica balsamina Linn is a well-known African traditional herb due to its tremendous medicinal and nutritional properties. It is used worldwide for the treatment of different ailments and diseases. In the present study, the phytochemical and antioxidant activity of South African M. balsamina fruit pulp extracts was evaluated. The fruit pulp extracts were obtained by using the serial exhaustive extraction procedure using the solvents hexane, DCM, acetone, and methanol. The resulting extracts were subjected to different standard colorimetric tests for phytochemical analysis. The presence of compounds with antioxidant activity was determined using dot plot and TLC. The DPPH radical scavenging assay, hydrogen peroxide activity, and reducing power assay, coupled with linear regression, were employed to determine the quantity of antioxidants and their IC50. The results for qualitative phytochemical screening have shown that the fruit pulp contains alkaloids, cardiac glycosides, saponins, phenolic compounds, tannins, flavonoids, terpenoids, and steroids. All the extracts revealed the presence of antioxidant activity in both dot plot and TLC. Acetone extracts (0.279 mg/mL) showed the lowest IC50 compared to the standards gallic acid (0.4 mg/mL) and diosgenin (0.42 mg/mL). These findings confirmed that M. balsamina is very rich in phytochemical compounds and has strong antioxidant potential; therefore, it could be a potential source of drugs which in the future may serve the production of synthetically improved therapeutic agents.